FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENYAKIT PNEUMONIA PADA ANAK DI RSU ROYAL PRIMA MEDAN - Liena Liena (Universitas Prima Indonesia, 2020)
Pneumonia is still be a health problem in children at this moment. Based on UNICEF’s data for the year 2016, pneumonia accounts for up to 16 per cent of children deaths. From the recorded population data, Indonesia is included in the top 10 countries with the mortality rate due to pneumonia in children under five years old, the eighth order in the year 2013. The purpose of this research was to determine the factors that related with pneumonia disease in child in Royal Prima General Hospital Medan Year 2016. This research was quantitative research with retrospective cohort study design. The population in this research is all of children patient with pneumonia disease who was recorded in the medical records in Royal Prima General Hospital Medan Year 2019. The analysis of data using univariate analysis and bivariate analysis. Based on the results of Chi-Square test showed that age statistically had no relation with pneumonia disease in children (p = 0,899; RR = 0,984; 95% CI = 0,7 – 1,2), gender statistically had no relation with pneumonia disease in children (p = 0,483; RR = 0,922; 95% CI = 0,7 – 1,1), and nutritional status statistically had relation with pneumonia disease in children (p = 0,000; RR = 2,582; 95% CI = 1,4 – 4,7). This research also suggests to children and family to pay more attention how to prevent and handle the factors that related to pneumonia disease in children.